Determination of Eruption Timings of Mandibular and Maxillary First Permanent Molar and its Association with BMI of Children - Sana Javed, Mahwash Malik Baloch, Muhammad Shoaib, Shuja Aslam, Asad Tahir, Abdul Ghani Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the association of eruption timing of the mandibular and maxillary first permanent molars with BMI of children in school children of Hyderabad. Subject and Methods: A total of 704 (364 boys 340 girls) school children from various government schools of Hyderabad city were enrolled in the study. All the children were in age range on 5 to 8 years. A dental examination was conducted to determine the presence of permanent mandibular and maxillary first molars. Children's height and weight were recorded in meters and kilograms, and their BMI was calculated. The SPSS version 22.0 was used to analyze the data Results: Out of 704, there were 364 (51.70%) boys and 340 (48.29%) girls. Mandibular 1st molar was the 1st tooth to erupt with mean age of 5.83±1.2 in boys and in girls it was 5.52±1.2. Most of the children were reported with normal weight as per BMI. Conclusion: An earlier median eruption timing was recorded for the mandibular permanent first molar compared to the maxillary permanent first molar. All the teeth examined in girls erupted earlier than in boys.